AB0096 Presence of ACPA and RF Autoantibodies in Ulcerative Colitis and Crohn's Disease. (15th July 2016) - Janssen, K.M.J.; Hop, H.; Vissink, A.; Dijkstra, G.; Brouwer, E.; Westra, J.
Abstract : Background: Presence of arthritis autoantibodies is specific for rheumatoid arthritis (RA). Anti-citrullinated peptide antibodies (ACPA) and rheumatoid factor (RF) can be detected several years before the onset of arthritis and are thought to have a pathogenic role. However, where and when autoantibody production starts is unclear. A potential trigger could be chronic mucosal inflammation as in inflammatory bowel disease (IBD) since the gut microbiome is thought to be involved in induction of (auto) immunity. This assumption is supported by the demonstration of citrullinated proteins in intestinal tissue of IBD patients. Objectives: To assess the prevalence of ACPA and RF in IBD patients as well as to assess the prevalence of joint complaints in autoantibody positive versus autoantibody negative IBD patients. Methods: Serum was collected from 227 patients with ulcerative colitis (UC) and 164 with Crohn's disease (CD) participating in the Dutch IBD pearl chain institute biobank initiative. Baseline disease characteristics including enthesitis, arthralgia, arthritis and comorbid conditions like spondylarthropathy were obtained from medical electronic records. IgG and IgA ACPA levels were measured by anti-CCP2 ELISA from EuroDiagnostica (ED) and IgM and IgA-RF levels were measured by in-house ELISA. The cut-off value for IgG ACPA positivity was 2 U/mL and for IgA ACPA 1.04 aU/ml based on the mean +2SD of a group of healthy reference samples. Seropositivity for IgM and IgA-RF was defined at ≥10 IU/ml and ≥25 IU/ml, respectively. Results: Thirty-two (14.1%) UC and 33 (20.1%) CD patients had an IgG ACPA level >2 U/ml. However, all IgG ACPA levels were below the diagnostic cut off level for RA which is set at ≥25 U/ml. IgA ACPA levels were increased in 83 (36.5%) UC and 48 (29.3%) CD patients. IgM-RF seropositivity was observed in 11 (4.8%) UC and 6 (3.7%) CD patients. IgA-RF seropositivity was observed in 6 (2.6%) UC and 8 (4.9%) CD patients. A total of 101 (44.5%) UC and 76 (46.3%) CD were seropositive for at least 1 arthritis autoantibody. Arthralgias were reported in 19.1% of UC and 33.3% of CD, respectively. Among patients with arthralgias, the percentage of individuals being seropositive for 1 or more autoantibodies was comparable to patients without arthralgias. Conclusions: The results of our study support the hypothesis that inflammation of intestinal mucosa induces low systemic levels of ACPA, which eventually may play a role in induction of RA. However, the development of arthralgias in IBD patients is independent on the presence of low systemic presence of arthritis autoantibodies. Disclosure of Interest: None declared